Persepsi Kualitas Layanan dan Kepuasan Pelanggan pada Pusat Perbelanjaan Kota Banda Aceh dengan Metode SERVQUAL - Munawir Munawir (Jurnal EMT KITA, 2018)
Service Quality have a lot of interests of researchers and practitioners and most believe that the quality of service can improve the performance of a company. The purpose of this study is to measure the relationship between service quality and customer satisfaction among customers in the shopping center of the Banda Aceh city. This research uses a SERVQUAL model was modified with the unique dimensions of compliance in the context of the service industry. The data collected from the 100 regulars or as a member at a shopping center. Sample data were analyzed statistically through confirmatory factor analysis using exploratory factor analysis (CFA) and structural equation modelling (SEM) analysis can determine the perceptions of service quality and customer satisfaction. The results showed that the scale of the multidimensional quality of service impacting positively and significantly related to the unidimensional scale of customer satisfaction. In addition, the dimensions of the SERVQUAL model response proves by showing the highest contribution factor in overall models. Furthermore, this research has practical implications for policy makers the shopping center to better understand customer behavior intentions.